PENGARUH DIMENSI KEPERCAYAAN TERHADAP KEPUTUSAN BERTRANSAKSI PELANGGAN E-COMMERCE DI INDONESIA - Rian Piarna; Tri Herdiawan Apandi (Jurnal Ilmiah Ilmu dan Teknologi Rekayasa, 2020)
The purposes of this research is to explain the influence of trust to transaction on e-commerce. This research conducted by taken samples on e-commerce customers in Indonesia. Main instrument on data collection is questionnaire which is distributed through social media (Facebook, Twitter, and Blogs) and measured by Likert Scale. Respondent amount on this research is 150 ecommerce customer in Indonesia. Analysis data used is Structural Equation Model (SEM). The result on this research showed that trust dimension has significant influence on e-commerce customers transaction decision.